Association of Vitamin D Deficiency and Diabetic Foot Ulcer Patients in Dr Mohammad Hoesin General Hospital Palembang - Dahlan, Kemas; Yususf, Fahmi Jaka; Irfannuddin, Irfannuddin; Murti, Krisna; Muradi, Akhmadu; Liberty, Iche Andriyani (Jurnal Sehat Indonesia (JUSINDO), 2025)
Vitamin D plays a role in the healing process of diabetic foot ulcers (DFU); it can improve the immune system, regulate inflammation function, and regulate growth factors in diabetes mellitus (DM). The immunomodulatory effects of vitamin D include reduced production of IL-2, IL-6, and TNF-alpha and increased production of IL-10. It also increases the activity of antimicrobial peptides (AMP) such as cathelicidin, and it promotes the differentiation of monocytes into macrophages, phagocytosis, and the production of lysosomal enzymes. Furthermore, vitamin D stimulates growth factors including vascular endothelial growth factor (VEGF) and transforming growth factor beta (TGF-β). In this study, the incidence of DM and DFU in DM patients at RSUP Dr. Mohammad Hoesin Palembang will be compared to serum vitamin D levels. This research uses quantitative methods with an analytical observational design. The Mean vitamin D serum level was 11,727 ng/mL, and there was a significant association between serum vitamin D deficiency and DFU (p-value; 0.036 < 0.05). There was a significant association between serum vitamin D deficiency and DFU occurrence (p-value; 0.036 < 0.05) in Mohammad Hoesin General Hospital Palembang. Based on the results of this study, we proposed that patients with diabetic foot ulcers should have their serum vitamin D levels checked, and that vitamin D should be given to them as part of their therapy.